Role of Vitamin A/Retinoic Acid in Regulation of Embryonic and Adult Hematopoiesis - Cañete, A; Cano, E; Muñoz-Chápuli, R; Carmona-Mejías, Rita María (MDPI, 2017)
Vitamin A is an essential micronutrient throughout life. Its physiologically active metabolite retinoic acid (RA), acting through nuclear retinoic acid receptors (RARs), is a potent regulator of patterning during embryonic development, as well as being necessary for adult tissue homeostasis. Vitamin A deficiency during pregnancy increases risk of maternal night blindness and anemia and may be a cause of congenital malformations. Childhood Vitamin A deficiency can cause xerophthalmia, lower resistance to infection and increased risk of mortality. RA signaling appears to be essential for expression of genes involved in developmental hematopoiesis, regulating the endothelial/blood cells balance in the yolk sac, promoting the hemogenic program in the aorta-gonad-mesonephros area and stimulating eryrthropoiesis in fetal liver by activating the expression of erythropoietin. In adults, RA signaling regulates differentiation of granulocytes and enhances erythropoiesis. Vitamin A may facilitate iron absorption and metabolism to prevent anemia and plays a key role in mucosal immune responses, modulating the function of regulatory T cells. Furthermore, defective RA/RARα signaling is involved in the pathogenesis of acute promyelocytic leukemia due to a failure in differentiation of promyelocytes. This review focuses on the different roles played by vitamin A/RA signaling in physiological and pathological mouse hematopoiesis duddurring both, embryonic and adult life, and the consequences of vitamin A deficiency for the blood system.
Keywords: Vitamina A; embryos; hematopoiesis; leukemia; retinoic acid; vitamin A; vitamin A deficiency